Nueva aproximación tafonómica al estudio de las marcas de corte para el debate de caza y carroñeo en yacimientos africanos: Aplicación al FLK Zinj (Olduvai, Tanzania) - Barba, Rebeca; Domínguez-rodrigo, Manuel (Complutum, 2008)
This work introduces a new experimental approach to the study of the behavioral meaning of cut marks as reflected by their actual location on bone sections. Upper limb bones and intermediate limb bones produce anatomically patterned distribution of flesh scraps (cold zones) after carnivore intial consumption of carcasses. Cut marks occurring in those bone sections devoid of scraps (hot zones) should be indicative of bulk defleshing. The present work shows an experimental quantification of cut marks on both zones within each of the long limb bone sections. The results are applied to the analysis of bone type/portion distribution of cut marks at the crucial site of FLK Zinj to discern hominid butchering behavior.
Keywords: Cut marks; Hot zones; Cold zones; Hunting versus scavenging; Taphonomy; Experimental archaeology